Kalisz interwar guides as a source of information about the city - Obała, Ewa (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The purpose of the article is to present Kalisz guides and catalogues of the interwar period that aroused constant interest of researchers due to their content. Their editorial shape and posted messages, despite appearances of elusiveness, carry important content, showing the image of the city’s life and activities, its institutions and residents. This type of publication contains a lot of historical information and tourist news, its layout favors easy navigation, and the extensive list of institutions and people shows the attractiveness of the city. The article draws attention to the variety of information contained in these publications and in its assumptions is to help the work of interested regionalist researchers. It also contributes to documenting Kalisz’s place among significant and developing production and commercial centers of the Second Polish Republic. The historical method was used in it, as well as existing extensive literature devoted to Kalisz in the interwar period.